PERBEDAAN HASIL BELAJAR MELALUI PENERAPAN MODEL INKUIRI TERBIMBING DAN STUDENT TEAM ACHIEVEMENT DIVISIONS PADA PELAJARANILMU PENGETAHUAN ALAM - Rais Hidayat; Ristinofa Ristinofa (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2017)
This research aims to improve the quality of the learning process and the result of learning process Thisresearch is a quasi experimental study. This research subject is class gared IV-A, IV-B and IV-C Public Elementary School Manggis Cicurug Sukabumi. Analysis technique used for pre-requisites analysis test which includes normality test, homogenity test, and hypothesis test using t-test. In the normality test with liliefors test showed that the class experiment 1 Ltestvalue is (0,144) with Ltable of (0,149), the class experiment 2 Ltestvalueis (0,074) with Ltable of (0,154), while the control class Ltestvalue is (0,151) with Ltable of (0,161), so that the value of Ltestfor all data ≤ than the value of Ltable with the significant standard is α= 0,05%, all data gives normal distribution. In the homogeneity with bartlett test Xtest value is (3,208) ≤ with Xtable of (5,991). In the hypothesis test with t-test showed that the class experiment 1 and the control class ttestvalue is (14,12) ≥ than ttable of (1,99394), the class experiment 2 ant the control class ttestvalue is (9,96) ≥ than ttable of (1,99962), while the class experiment 1 and the class experiment 2 ttestvalue is (2,83)≥ than ttable of (1,99656), therefore all the data showed that H0 rejected and Ha accepted. Based on this research, it can be concludedthat there are differences of result between the using cooperative learning model guided inquiry and student teams achievement divisions.